2004
DOI: 10.1152/ajpregu.00328.2003
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the DMH selectively inhibits the ACTH and corticosterone responses to hypoglycemia

Abstract: We have previously reported that repeated bouts of insulin-induced hypoglycemia (IIH) in the rat result in blunted activation of the paraventricular, arcuate, and dorsomedial hypothalamic (DMH) nuclei. Because DMH activation has been implicated in the sympathoadrenal and hypothalamic-pituitary-adrenal (HPA) responses to stressors, we hypothesized that its blunted activation may play a role in the impaired counterregulatory response that is also observed with repeated bouts of IIH. In the present study, we eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 45 publications
2
21
1
Order By: Relevance
“…We found that staining for GFP-positive neurons was primarily within the VMH with a small amount of spread to the DMH, the latter predominantly via the needle track. The DMH is a glucose-sensing region, however, its chemical inactivation in vivo with lidocaine results in a mild impairment of adrenocorticotrophin hormone (ACTH) and corticosterone response to acute hypoglycemia only (38). In contrast, in the present study, AMPK downregulation in the VMH resulted in reduced epinephrine and glucagon responses to acute hypoglycemia and had no effect on the corticosterone response.…”
Section: Discussioncontrasting
confidence: 75%
“…We found that staining for GFP-positive neurons was primarily within the VMH with a small amount of spread to the DMH, the latter predominantly via the needle track. The DMH is a glucose-sensing region, however, its chemical inactivation in vivo with lidocaine results in a mild impairment of adrenocorticotrophin hormone (ACTH) and corticosterone response to acute hypoglycemia only (38). In contrast, in the present study, AMPK downregulation in the VMH resulted in reduced epinephrine and glucagon responses to acute hypoglycemia and had no effect on the corticosterone response.…”
Section: Discussioncontrasting
confidence: 75%
“…However, the role of the THPVP may be more complex than originally hypothesized. First, control PBS infusions in SH rats experiencing a single (naive) bout of hypoglycemia had no effect on the neuroendocrine responses, when compared with other data from our laboratory in this model, in subjects with no CNS cannulas (Evans et al, 2001), or identical experimental protocols where cannulas were aimed at the paraventricular or dorsomedial nuclei of the hypothalamus (Evans et al, 2003(Evans et al, , 2004. Likewise, acute LIDO infusions in SH rats had no effect on the neuroendocrine responses.…”
Section: Discussionmentioning
confidence: 82%
“…Prior to performing experiments, animals were familiarized with square acrylic test chambers (∼30 cm×30 cm×30 cm) and the microinjection procedure as described by Evans et al (2003Evans et al ( , 2004. Subsequent to this, the animals were placed in the test chambers for at least 2 h before experimental procedures began.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, administration of the GABA A receptor antagonist into the VMH did not alter corticosterone responses. This finding suggests that glucagon and epinephrine responses may be primarily regulated through the VMH, whereas activation of the hypothalamo-pituitaryadrenal response to hypoglycemia is mediated through other hypothalamic centers, such as the paraventricular nucleus (46,47).…”
Section: Discussionmentioning
confidence: 99%